Skrb dekana Vendela Ratkoviča in dekanijske komisije za čistejši jezik v Málem katekizmusu Mikloša Luttarja iz leta 1888 - Smej, Jožef (Slavistična revija, 2001)
Milo Luttar, a teacher at the public school in Gančani, adapted the bilingual Máli katekizmus, containing 32 pages in the Prekmurje Slovene dialect and 32 pages in Hungarian. It was printed in 1888 in Murska Sobota. The article attempts to show how Vendel Ratkovič, the Slovenska Okroglina dean, together with the deanery committee, examined the Catechism and suggested corrections and improvements in the Prekmurje text.
Keywords: katekizmi; Luttar, Mikloš; prevodi; Ratkovič, Vendel; Slovene; slovenščina; zgodovina slovenskega jezika